The role of women in self-actualizing in the life of the community of Medan city - Aisyah, Nur (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
North Sumatra has a population of 14.8 million, and Medan Municipality has a population of 2.4 million, consisting of 1.21 million men and 1.22 million women. The number of women is more than men, with the assumption that women are more likely to show self-actualization. The purpose of this study is how the role of women in self-actualization in the life of the people of Medan city. This research uses data collection methods through qualitative methods, case studies, interviews through informants. Researcher analysis using data reduction techniques, namely summarizing, selecting, and focusing on the things that are needed. The results showed that women's self-actualization is the potential a person has to realize and maximize their potential, especially in women. In this case, women who are members of the IWAPI Organization, FKMI, have chosen and determined the choice of organization as the right forum. Therefore, they can position themselves as women who actualize themselves. Women's self-actualization in IWAPI, FKMI organizations is not hampered by government regulations or discriminatory government policies. Based on the observation and documentation data of women researchers from the IWAPI, FKMI organizations that along with the impact of the COVID-19 pandemic, encourage self-improvement through self-actualization in family and community life in Medan city.